Role of cortical microbleeds in cognitive impairment: In vivo behavioral and imaging characterization of a novel murine model. Issue 6 (June 2019) - Bergeron, Sandrine; Chen, Yaohua; Auger, Florent; Deguil, Julie; Durieux, Nicolas; Skrobala, Emilie; Barus, Romain; Potey, Camille; Cordonnier, Charlotte; Pasquier, Florence; Ravasi, Laura; Bordet, Régis; et al.
Cerebral microbleeds (CMBs) could contribute to cognitive impairment in the general population and in patients with dementia. We designed a study to (i) develop a murine model of CMBs, (ii) assess whether CMBs affect cognition in this model and (iii) assess whether this model is sensitive to pharmacological modulation. Male C57Bl6/J mice were stereotactically administered collagenase to induce cortical lesion analysed by MRI at 24 h. CMB-mice were assessed at six weeks post-lesion for cognitive performances (Barnes maze and Touchscreen automated paired-associated learning (PAL) task) and for cerebral metabolism (in vivo PET/CT with fluorodeoxyglucose (FDG)). CMB-model sensitivity to pharmacological modulation was assessed by administering atorvastatin (5 mg/kg/day) over the follow-up period. CMB mice were compared to naïve littermates. Collagenase at 0.8 µU/µl appeared suitable to induce reproducible and reliable CMBs. At six weeks, a decline in learning, spatial and visuospatial memory was significantly observed in CMB-mice. Brain metabolism was impaired in all cortex, striatum and the ipsilateral dentate gyrus. A significant improvement in cognition performances was depicted under atorvastatin. In this novel murine model of CMBs, we validated that CMBs lowered cognitive performances and affected regional metabolism. We also proved that this CMB-model is sensitive to pharmacological modulation.